2018
DOI: 10.1002/hfm.20732
|View full text |Cite
|
Sign up to set email alerts
|

Ergonomics study and analysis of workstations in Tunisian mechanical manufacturing

Abstract: The workers’ performance in the mechanical manufacturing sector is the main factor for the improvement of productivity and quality. At present, it seems that the available information on the ergonomics and the working environment of the mechanical manufacturing actors is scarce. This study deals with the relationship between the working method and the workstation in injection mold manufacturing. An original methodology, based on the survey of operators using participatory ergonomic tools, is proposed in order … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
19
0
1

Year Published

2019
2019
2022
2022

Publication Types

Select...
4
2

Relationship

1
5

Authors

Journals

citations
Cited by 30 publications
(24 citation statements)
references
References 41 publications
0
19
0
1
Order By: Relevance
“…One of them, the RULA method, is also used to analyse repetitive movements (associated with REBA) [6]. Due to these considerations, some studies present a broader and more complete analysis [46,66].…”
Section: Combination With Other Methodsmentioning
confidence: 99%
See 1 more Smart Citation
“…One of them, the RULA method, is also used to analyse repetitive movements (associated with REBA) [6]. Due to these considerations, some studies present a broader and more complete analysis [46,66].…”
Section: Combination With Other Methodsmentioning
confidence: 99%
“…In the first case, this was achieved by means of simulations and, in the second, by means of photographs. Subsequently, several authors again combined methods (OWAS, RULA and REBA) [66,76] in iron and steel operations that involved milling, turning and drilling.…”
Section: Metallurgical Sectormentioning
confidence: 99%
“…The operators subjected to the ergonomic study were identified in Table 12, which lists the appropriate tasks. Each maintenance operation was divided into tasks containing each of the subtasks, as depicted by Boulila et al (2018). Table 13 presents the NSCs obtained for each maintenance task.…”
Section: Comfort Level Assessmentmentioning
confidence: 99%
“…Some of them can be used for a general assessment; others can focus on the assessment of a specific risk factor in the context of a professional task. The tools list included mainly the following methods for: Analyzing awkward body postures such as Rapid Upper Limb Assessment (RULA; McAtamney & Corlett, ), Rapid Entire Body Assessment (REBA; Hignett & McAtamney, ) and Ovako Working Posture Assessment (Karhu, Kans, & Kuorinka, ). Evaluating manual material handling activities such as NIOSH Lifting Equation (Waters, Putz‐Anderson, Garg, & Fine, ). Evaluating comfort level assessment such as Body Parts Symptoms Survey (BPSS; Corlett & Bishop, ).Another motivation for evaluating discomfort movement is the development of digital human models for the ergonomic design of products, as described by Alkan, Vera, Ahmad, Ahmad, and Harrison (), Boulila, Ayadi, and Mrabet (), and Qutubuddin, Hussain, Kumar, and Reddy (). Thanks to recent progress, it has become easier for ergonomics experts to assess human factors in the planning phase before the design of the workstation (Prádanos, et al, ; Sutari, Nugroho, Yekti, Astuti, & Sari, ).…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation